The Investigation of Indonesian EFL Learners’ Perception and Understanding on Equality Values in “Jane Eyre” Novel: A Gender Perspective - Rahman Hakim; Siti Suharsih; Rosmania Rima; Dhafid Wahyu Utomo; Dina Rachmawati (English Department - University of Sultan Ageng Tirtayasa, 2021)
This research investigated the Indonesian EFL Learners’ perception and understanding of gender equality values in one of the greatest novels, Jane Eyre, written by Charlotte Bronte in 1847 as the picture of women emancipation at the time. To this aim, 100 Indonesian pre-intermediate EFL learners were selected from among 125 students at one of the public universities in Banten. They were given a questionnaire and it was analyzed descriptively to explore the content of the story, equality values and the connection with the value of life. The analysis of the data revealed that first, there is still gender inequality between men and women. Second, self-expression, employment, and education were dominant themes found in the issues of gender inequality in the novel. Third, the gender values in the novel “Jane Eyre” are still related to the current reality or the environment. Moreover, extensive reading activities were impactful in rising students’ interest in reading and awareness of social issues. Therefore, this study suggests that the values of gender equality can be brought to be a good discussion in the class through extensive reading activities.